2002
DOI: 10.1002/glia.10035
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and differential expression of tau mRNA isoforms as oligodendrocytes mature in vivo: Implications for myelination

Abstract: Oligodendrocytes and neurons derive from the same cell type but develop distinct morphologic and functional properties as they mature in vivo. Both cells express tau protein, a developmentally regulated protein in the central nervous system. The regulation of tau has been investigated extensively in neurons but not in oligodendrocytes, so we studied regulation of tau in oligodendrocytes in vivo. The amino-derived tau isoforms consist of isoforms with zero (A0), one (A1), or two (A2) inserts. We examined the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 61 publications
1
39
0
Order By: Relevance
“…Isotype-specific C-terminals interact differentially with some MAPs (Paschal et al, 1989;Cross et al, 1994), and isotype-related differences in MAP-promoted MT assembly have been reported (Banerjee et al, 1992;Lu and Luduena, 1994). Oligodendrocytes upregulate MAP-1B (Fischer et al, 1990;Vouyiouklis and Brophy, 1993), MAP-2c (Muller et al, 1997;Richter-Landsberg and Gorath, 1999), MAP-2e (also called MAP2þ13; Shafit-Zagardo et al, 1999, MAP-4 (Vouyiouklis and Brophy, 1995), and the four-repeat tau isoforms (Richter-Landsberg and Gorath, 1999;LoPresti, 2002) during myelination. Enrichment for b IV tubulin and these MAPs may promote formation of an MT network with stability and transport characteristics necessary for myelination.…”
Section: Discussionmentioning
confidence: 98%
“…Isotype-specific C-terminals interact differentially with some MAPs (Paschal et al, 1989;Cross et al, 1994), and isotype-related differences in MAP-promoted MT assembly have been reported (Banerjee et al, 1992;Lu and Luduena, 1994). Oligodendrocytes upregulate MAP-1B (Fischer et al, 1990;Vouyiouklis and Brophy, 1993), MAP-2c (Muller et al, 1997;Richter-Landsberg and Gorath, 1999), MAP-2e (also called MAP2þ13; Shafit-Zagardo et al, 1999, MAP-4 (Vouyiouklis and Brophy, 1995), and the four-repeat tau isoforms (Richter-Landsberg and Gorath, 1999;LoPresti, 2002) during myelination. Enrichment for b IV tubulin and these MAPs may promote formation of an MT network with stability and transport characteristics necessary for myelination.…”
Section: Discussionmentioning
confidence: 98%
“…Although direct evidence for specific S100B functions during OL differentiation is still missing, it is known that, during their maturation, OLs develop cytoplasmic extensions and flat membranous sheets that contain an extensive cytoskeletal network of microtubules (RichterLandsberg, 2001). OLs express the MT-associated proteins MAP2 and tau (LoPresti, 2002), whose phosphorylation by protein kinase II is inhibited in vitro in a calcium-dependent manner by S100B (Baudier and Cole, 1988). Therefore, we predict a role for S100B in regulating OL cell shape that is consistent with its documented association with microtubular structures in cultured oligodendrocytes (Richter-Landsberg and Heinrich, 1995;Sorci et al, 2000).…”
Section: /Neunmentioning
confidence: 98%
“…In contrast, missorting of tau causes reduced myelin and axonal degeneration (Figure 1). To understand which levels of tau regulation in OLGs can be targeted, several studies have established the importance of tau mRNA splicing and of tau posttranslational modifications [9,13,33,34,35]. These events are key to understand how tau can promote either CNS health or disease.…”
Section: Mechanisms Of Tau Regulationmentioning
confidence: 99%
“…These events are key to understand how tau can promote either CNS health or disease. Tau mRNA splicing is highly regulated and, in a cell-specific pattern [13]. Contrary to the pattern of neuron regulation, which has a developmentally regulated shift in the tau mRNA form expressed in the young versus adult rodent CNS, tau regulation in OLGs is specific to these cells, with the persistent presence in the adult CNS of forms of tau mRNA splicing that are abundant in neonatal neurons.…”
Section: Mechanisms Of Tau Regulationmentioning
confidence: 99%
See 1 more Smart Citation